The Influence Secretarial Competence, Self-Esteem & Self-Efficacy of The Work Readiness of Final Year Students - Lusyiana, Alsya; Christian Wiradendi Wolor; Marsofiyati (Business and Investment Review, 2023)
Research Aims: The purpose of this study was to determine the effect of secretary competence, self-esteem and self-efficacy on work readiness in final semester students, especially in the department of office administration education, Jakarta State University. Design/Methodology/Approach: This research uses quantitative methodology. Research Findings: Basically, job readiness is an important thing for students who will graduate and have been declared graduated from college. Work readiness indicates that there is an individual transformation of students from the world of education to the company sector and are ready to face the world of work. One of the students' job readiness can be influenced by soft skills, which can be seen that soft skills are needed in aspects of planning and the job search process and success in pursuing a job career. In the current era of the industrial revolution 4.0, students are expected to be ready for all conditions in the field, they must be mentally and intellectually tested and intellectual. Instead of providing job readiness soft skills, skills, knowledge, organizational or work experience are also highly seen by employers. Because from a worker who is ready to carry out the assigned work and is responsible, human resources emerge who are ready to build a company well and to increase competitiveness for other offices.The purpose of this study is to obtain empirical data on variables that affect the job readiness of final year students majoring in office administration education UNJ, as for the specific research objectives, namely: knowing the influence of secretarial competence self esteem and self efficacy.